1999
DOI: 10.1111/j.1745-6584.1999.tb00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground Water Salinization Caused by Residual Neogene and Pliocene Sea Water‐An Example from the Judea Group Aquifer, Southern Israel

Abstract: The Judea Group Aquifer of late Albian‐Turonian age is mainly composed of karstic limestone and dolomite. In the western part of Israel it is known as the Yarkon‐Taninim ground water basin. The study area is located in the southern part of the basin. Fresh ground water (46 to 200 mg/L Cl) flows northward from the south and southeast. Saline ground water (1200 to 8350 mg/L Cl), which occurs irregularly in the midst of this flowpath, severely jeopardizes the development and exploitation of this aquifer. By defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Another plausible source of salinity could be unflushed seawater in the subsurface of northern Sinai and western Negev. According to Rosenthal et al (1999) the post-Messinian (Lower Pliocene) transgression penetrated inland (into northern Sinai, the western Negev and into the Coastal Plain of Israel) both through erosional channels, which were incised during the Neogene, and inundating outcrops of permeable formations (Zilberbrand et al, 2005). In view of the absence of halite dissolution (as indicated by the models - Table 5), it is plausible that in the studied areas seawater could have penetrated inland through the upper parts of the channels which are rich in beds of gypsum, but contain no halite (Fleischer, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Another plausible source of salinity could be unflushed seawater in the subsurface of northern Sinai and western Negev. According to Rosenthal et al (1999) the post-Messinian (Lower Pliocene) transgression penetrated inland (into northern Sinai, the western Negev and into the Coastal Plain of Israel) both through erosional channels, which were incised during the Neogene, and inundating outcrops of permeable formations (Zilberbrand et al, 2005). In view of the absence of halite dissolution (as indicated by the models - Table 5), it is plausible that in the studied areas seawater could have penetrated inland through the upper parts of the channels which are rich in beds of gypsum, but contain no halite (Fleischer, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…This transgression reached eastwards to the foothills of the Judea and Samaria Mts. Rosenthal et al (1999) and Livshitz (1999) suggested that the saline groundwaters, nowadays irregularly distributed in the Judea and Avdat beds in the subsurface of these areas, could be relicts of this marine transgression. The Cl content of these waters does not exceed 21 g/L and the relevant equivalent ratios (Mg/Ca, Na/Cl and Cl/Br weight ratio) are typical of sea water.…”
Section: Pleistocenementioning
confidence: 97%
“…The resultant brine permeated the permeable rock sequence into which canyons incised. According to Rosenthal et al (1999), these brines penetrated into the permeable calcareous Arad (upper part), Kurnub and Judea Groups from which previously formed fluids were drained and flushed out during the major Oligocene uplift and the following Miocene structural events. The western parts of the country were progressively covered by the transgressing sea depositing the argillaceous Yafo Formation.…”
Section: Pliocenementioning
confidence: 99%
“…Salts and brines also accumulated in the canyon-like channels of the Kishon-Yizreel-Bet Shean Valleys in the north and the Afik-Beer Sheva channel in the south through which seawater penetrated into the Rift creating the Sdom Sea (Rosenthal et al 1999). At present, remnants of highly saline brines are still present in deep sub-basins of the Mediterranean Sea (Vengosh et al 1994a;Bau et al 1997).…”
Section: Scenario Of the Late Sdom Seamentioning
confidence: 98%
“…During the Mio-Pliocene, brines were mainly generated by the post-Messinian ingression of seawater, which dissolved evaporites previously deposited on the dried-up Mediterranean Sea bed and in the erosive channels incised into the adjoining coastal areas (Rosenthal et al 1999;Hirsch 2005a, b). In addition, brines reacted with the invaded rock sequence and with contemporaneous basic volcanics.…”
Section: Introductionmentioning
confidence: 99%